Does Government Spending Efficiency Improve Human Development in Sulawesi? - Bella Dwi Septi Martia; Ratu Eva Febriani (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
We evaluate the impact of government spending efficiency on achievement in quality of human life for a panel of 78 counties of the Sulawesi region during 2015-2021. We compute the magnitude efficiency counts by Data Envelopment Analysis (DEA) to answer the research question. The inputs are government spending on education, health, economics, and social protection. The output used the human development index. The findings reveal that Makassar is the most efficient county over the period to encourage the human development index. Otherwise, Jeneponto is the most inefficient county. Furthermore, some county's flexibility changed from efficient to inefficient in using spending to raise the human development index.